COVID-19 vaccination-related adverse events among autoimmune disease patients: results from the COVAD study. (17th June 2022) - Sen, Parikshit; Ravichandran, Naveen; Nune, Arvind; Lilleker, James B; Agarwal, Vishwesh; Kardes, Sinan; Kim, Minchul; Day, Jessica; Milchert, Marcin; Gheita, Tamer; Salim, Babur; Velikova, Tsvetelina; et al.
Abstract: Objectives: COVID-19 vaccines have been proven to be safe in the healthy population. However, gaps remain in the evidence of their safety in patients with systemic autoimmune and inflammatory disorders (SAIDs). COVID-19 vaccination-related adverse events (AEs) in patients with SAIDs and healthy controls (HC) seven days post-vaccination were assessed in the COVAD study, a patient self-reported cross-sectional survey. Methods: The survey was circulated in early 2021 by >110 collaborators (94 countries) to collect SAID details, COVID-19 vaccination details and 7-day vaccine AEs, irrespective of respondent vaccination status. Analysis was performed based on data distribution and variable type. Results: Ten thousand nine hundred respondents [median (interquartile range) age 42 (30–55) years, 74% females and 45% Caucasians] were analysed; 5867 patients (54%) with SAIDs were compared with 5033 HCs. Seventy-nine percent had minor and only 3% had major vaccine AEs requiring urgent medical attention (but not hospital admission) overall. Headache [SAIDs = 26%, HCs = 24%; odds ratio (OR) = 1.1 (95% CI: 1.03, 1.3); P = 0.014], abdominal pain [SAIDs = 2.6%, HCs = 1.4%; OR = 1.5 (95% CI: 1.1, 2.3); P = 0.011], and dizziness [SAIDs = 6%, HCs = 4%; OR = 1.3 (95% CI: 1.07, 1.6); P = 0.011], were slightly more frequent in SAIDs. Overall, major AEs [SAIDs = 4%, HCs = 2%; OR = 1.9 (95% CI: 1.6, 2.2); P < 0.001] and, specifically, throat closure [SAIDs = 0.5%, HCs = 0.3%; OR = 5.7 (95% CI: 2.9, 11); P = 0.010] were more frequent in SAIDs though absolute risk was small (0–4%). Major AEs and hospitalizations (<2%) were comparable across vaccine types in SAIDs. Conclusion: Vaccination against COVID-19 is safe in SAID patients. SAIDs were at a higher risk of major AEs than HCs, though absolute risk was small. There are small differences in minor AEs between vaccine types in SAID patients.